how does lim t*e^t t--> - infinity = lim t/e^-t t--> - infinity how does the e^t turn into e^-t in the denominator?? THANKS
Follow Math Help Forum on Facebook and Google+
Originally Posted by calculus0 how does lim t*e^t t--> - infinity = lim t/e^-t t--> - infinity how does the e^t turn into e^-t in the denominator?? THANKS Its a rule of exponents: ...
is there an explanation or proof? or do i just have to memorize this. thank youu
Originally Posted by calculus0 is there an explanation or proof? or do i just have to memorize this. thank youu You can think of it this way. Observe that . Thus, we see that either or . In our case, we want the latter result. Does this clarify things a little bit?
OHH. ok. makes perfect sense!! thankss
View Tag Cloud